Significance of Baseline and Changes of Tumor Markers and Neutrophil-to-Lymphocyte Ratio in Predicting Overall Survival for Patients with Advanced Pancreatic Adenocarcinoma: A Retrospective Analysis - Makoto Kadokura; Keisuke Tanaka; Fumitake Amemiya; Shinichi Takano; Mitsuharu Fukasawa; Nobuyuki Enomoto (Journal of Cancer Research and Practice)
Background: The usefulness of various prognostic factors for pancreatic cancer has been reported, but limited studies have focused on these changes during chemotherapy. The purpose of the present study was to investigate the prognostic factors and to evaluate the significance of these changes during chemotherapy in patients with advanced pancreatic cancer (APC). Materials and Methods: We retrospectively analyzed 213 patients with APC who underwent chemotherapy between January 2006 and December 2018 at Kofu Municipal Hospital and University of Yamanashi Hospital. Univariate and multivariate cox regression models were applied to investigate independent prognostic factors. Results: Multivariate analysis revealed that Eastern Cooperative Oncology Group Performance Status 2 (hazard ratio [HR] 4.07, P < 0.01), neutrophil-to-lymphocyte ratio (NLR) ≥3.9 (HR 1.97, P < 0.001), modified Glasgow prognostic score 1–2 (HR 2.77, P < 0.001), carcinoembryonic antigen ≥5.0 (HR 1.44, P = 0.026), carbohydrate antigen 19-9 ≥37 (HR 1.83, P = 0.004), ΔNLR >0 (HR 2.01, P < 0.001), ΔCEA (subtracting the baseline from the start of second cycles of chemotherapy) >0 (HR 1.64, P = 0.002), and ΔCA19-9>0 (HR 1.77, P = 0.002) were independent negative prognostic factors. Conclusion: Baseline and change in tumor markers and NLR are useful in predicting overall survival in APC patients undergoing chemotherapy.